Groundwater governance under climate change in India: lessons based on evaluation of World Bank interventions - Shiferaw, B. A.; Reddy, V. R.; Sharma, Bharat (Informa UK Limited, 2024)
Groundwater is the single largest source of water for irrigation and domestic use in India. Climate change further exacerbates the threat of depletion, reducing food security and increasing the vulnerabilities of resource users. Governance is complicated by externalities associated with its attributes as an invisible and fluid resource which create problems of rivalry and exclusion. Based on theory-based case studies for evaluation of selected World Bank projects, we analyse challenges for groundwater governance and identify factors that contribute to depletion. It highlights the need for integrating and balancing demand and supply-side approaches, including water-efficient irrigation and climate-smart practices.